PENGELOLAAN MANAJEMEN SUMBER DAYA MANUSIA DEMI MENINGKATKAN PRODUKTIVITAS KERJA PADA KANTOR UNIT PENYELENGGARA PELABUHAN ATAPUPU KABUPATEN BELU PROPINSI NUSA TENGGARA TIMUR - Rinawati Br Perangin-Angin (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2018)
One of the important unsure in organization is Human Resources Management. It meansthat organization based on the relation between human and many aspec in implamentation ofvision and mision organization. Human Resources Management becomes one of theimprotant unsure as indicators for job produktivity in Office unit of Atapupu port and OfficeUnit of wini port.Human resources management is Spesific Office of Atapupu Port.It becomes indicators forjob productivity to manage transportation at the Atapupu Port and Wini Area Working Areain North-Middle Timor Regency. Both of this ports must be handled by itself with humanresources management be better because they have an urgen positions that should be makeimpact to big responsibility to the Spesific Office of Atapupu Port.The job productivity is based by some aspects. That aspects are planning, implementation,evaluation, self-development, and compensation.Management of Human resources throughgood planing will give impact for public services.